NON-MOYAMOYA BILATERAL MIDDLE CEREBRAL ARTERY AGENESIS MIMICKING MULTIPLE SCLEROSIS - Bashir, Qasim; Badruddin, Aamir; Arif, Saeed; Hersonsky, Tamir (Journal of Ayub Medical College Abbottabad, 2013)
We present a case of a 41-year-old woman who carried the misdiagnosis of multiple sclerosis for 13 years while on disease modifying therapy [DMT]. Her neurologic work-up showed an extremely rare type of bilateral middle cerebral artery occlusive disease, a basilar apex aneurysm and paroxysmal atrial fibrillation. A thorough search for alternative neurologic diagnosis is recommended before patients are given a definitive diagnosis and committed to DMT